Enhancing Evidence-Based Practice Through University–Practitioner Partnerships. Issue 1 (January 2018) - Martin, Ian; Zyromski, Brett; Gigliotti, Edward W.
This article proposes a three-step model for implementing successful university and practitioner partnerships to advance the use of evidence-based practices (EBP) in school counseling. Although an ethical mandate exists to use EBP, many school counselor educators and school counselors struggle to implement EBP in their coursework or at their schools. The university–practitioner partnership model proposed here emphasizes that EBP be taught in coursework, that students reinforce those practices through observation of practitioners using them in their schools, and that students experiment with EBP in their fieldwork. We provide suggestions to support successful implementation of the model.